Peranacangan Film Dokudrama sebagai Promosi Tari Randai Saedar Siti - Fariz Firdaus, Dr. Syafwandi, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
This journal was created to create a medium for promoting the dance of Randai Saedar Siti in the form of dukudrama films which were made as the main media. The design of dokudrama film media as a medium for the promotion of randai dance. Saedar, the Minangkabau cultural tradition. With the delivery of information through the media film dokudrama is expected to be responded well by the public. Through this dokudrama film, it is hoped that it can be made as a document to make education about the Saedar Siti randai dance. The design of the dokudrama film as a promotion of randai saedar siti dance requires providing all matters related to randai Saedar Siti, namely discussing how the Minangkabau traditional cultural values and the noble values contained in the story of randai saedar siti dance. The design of the dokudrama film as a promotion of the SaedarSiti randai dance was carried out using the FOUR D. design method. Also through a research process that involved collecting data by observing, interviewing and studying literature. The data is then used to develop stories and basic concepts of visual communication such as cinematography, picture taking angles, to be applied so that they can be easily accessed by the target audience.Keywords: film, docudrama, promotion, dance and culture.